Vibrating Mesh Nebulisation of Pro-Antimicrobial Peptides for Use in Cystic Fibrosis - Éanna Forde; Graeme Kelly; Louise Sweeney; Deirdre Fitzgerald-Hughes; Ronan MacLoughlin; Marc Devocelle (MDPI AG, 2019)
Background: There has been considerable interest in the use of antimicrobial peptides (AMPs) as antimicrobial therapeutics in many conditions including cystic fibrosis (CF). The aim of this study is to determine if the prodrugs of AMPs (pro-AMPs) can be delivered to the lung by a vibrating mesh nebuliser (VMN) and whether the pro-AMP modification has any effect on delivery. Methods: Physical characteristics of the peptides (AMP and pro-AMP) and antimicrobial activity were compared before and after nebulisation. Droplet size distribution was determined by laser diffraction and cascade impaction. Delivery to a model lung was determined in models of spontaneously-breathing and mechanically-ventilated patients. Results: The physical characteristics and antimicrobial activities were unchanged after nebulisation. Mean droplet size diameters were below 5 μm in both determinations, with the fine particle fraction approximately 67% for both peptides. Approximately 25% of the nominal dose was delivered in the spontaneously-breathing model for both peptides, with higher deliveries observed in the mechanically-ventilated model. Delivery times were approximately 170 s per mL for both peptides and the residual volume in the nebuliser was below 10% in nearly all cases. Conclusions: These results demonstrate that the delivery of (pro-)AMPs to the lung using a VMN is feasible and that the prodrug modification is not detrimental. They support the further development of pro-AMPs as therapeutics in CF.